Stereotypical Representations of Female Characters in Film and Television in the Context of the Male Gaze and Their Breakthrough - Wang, Ruiqi; Liu, Zhishan (Transactions on Social Science, Education and Humanities Research, 2023)
By the end of the 19th century, the first wave of feminism emerged, advancing the plea and perspective of gender equality. This introduced feminism to the public’s attention for the first time. With the development of diverse media as well as the cultivation and awakening of female consciousness, this has led to an increasing demand for female-oriented works in the fields of art, film, and other cultural and spiritual domains. However, in the context of the entire patriarchal society, many, including artists, remain susceptible to the influence of misogyny. As a result, there’s a conscious or passive tendency to prioritize males, women are often easily regarded as the ’gazed-upon’ other. Consequently, female characters in many films and television shows continue to be portrayed with certain stereotypes. This paper briefly discusses the definitions of feminism and male gaze, taking numerous classic Chinese films and television works as examples to analyze the portrayal of female characters under the male perspective. In film and television works, we should analyze and reflect on the three dimensions of women’s ’othering’, demonization, and sexualization. In recent years, through analyzing films and television productions related to women’s awakening, we can observe how female characters progressively break free from the stereotypical impressions under the male gaze, finding their own path. The final conclusion drawn is that the plight of women begins with breaking free from the stereotypical perceptions of women within the male-dominated linguistic framework and male perspective and the process of self-affirmation of women’s identity begins. It is encouraged that all professionals in the film and television industry, as well as all women, make every effort in liberating women. It is hoped that cinematic and television productions can revolve around the intrinsic value of women, creating self-empowered female characters.